Effect of Levonorgestrel Implant on Lactation and Infant Growth: A Review: Review : Pengaruh Implan Levonorgestrel pada Laktasi dan Pertumbuhan Bayi - Febrianti, Yosi; Hanifah, Suci; Febrian, M. Pandoman; Annisa, Lily; Azza, Lintang Prava; Mafruhah, Okti Ratna; Medisa, Dian; Sari, Chynthia Pradiftha (Universitas Tadulako, 2024)
Background: Family Planning is a way to regulate the number of children born and the spacing of pregnancies through information, education, and the use of contraceptives. Postpartum contraception is important to obtain an optimal interpregnancy interval. Postpartum contraception should be initiated early; one of which is Long-Acting Reversible Contraception (LARC). Levonorgestrel can be used to prevent pregnancy because it interferes with ovulation, implantation, and fertilization. Objectives: This study aimed to assess the efficacy and effects of using levonorgestrel implants on breastfeeding and infant growth. Methods: Primary data were in the form of research papers obtained from PubMedÂ®, and Google ScholarÂ® published from the period 2010-2018. The keywords for the searches included: â€œlevonorgestrelâ€, â€œlevonorgestrel (LNG)-releasing implantâ€, â€œlevonorgestrel on lactogenesisâ€, â€œlevonorgestrel on infant growthâ€, and â€œlevonorgestrel on breastfeedingâ€, which were used alone or in combination. Results: The 20 selected articles were reviewed based on five identified phrases. Levonorgestrel subdermal implants were shown to be a good choice for women who wanted effective contraception. When used by breastfeeding mothers, levonorgestrel subdermal implants affected neither infant growth (0-1 year of age) nor lactation duration. Conclusions: Levonorgestrel subdermal implants can be effective long-term contraception. These implants are safe for breastfeeding mothers and do not affect infant growth.